2013
DOI: 10.1108/ijchm-10-2012-0187
|View full text |Cite
|
Sign up to set email alerts
|

Is the gaming industry still recession-proof?

Abstract: Purpose – The purpose of this study is to examine how the recent recession affected Iowa's gaming industry by analyzing gaming volumes before and through the recession. Design/methodology/approach – This study used autoregressive integrated moving average (ARIMA) with intervention analysis to examine Iowa statewide aggregated monthly slot coin-in, table drop, and admission from December 2001 through June 2012. Findings – The results of analyses show that: slot coin-in was not affected by the recession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Statistical analysis further indicated that the monthly average gaming volume, which includes table drop and coin-in, depicted only a relatively minor drop in Indiana during the 2007-2009 period compared to the monthly average gaming volume during 1999-2007; this difference was not statistically significant. The results of statistical analysis of gaming volume in Indiana are remarkably similar to the results of the Zheng et al (2013) investigation into gaming volume in Iowa, another nondestination gaming state. That study found a statistically significant decrease in table game drop but as table games represented such a small portion of drop-in repeater markets, the number of table games dollars lost due to the recession was not practically significant.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Statistical analysis further indicated that the monthly average gaming volume, which includes table drop and coin-in, depicted only a relatively minor drop in Indiana during the 2007-2009 period compared to the monthly average gaming volume during 1999-2007; this difference was not statistically significant. The results of statistical analysis of gaming volume in Indiana are remarkably similar to the results of the Zheng et al (2013) investigation into gaming volume in Iowa, another nondestination gaming state. That study found a statistically significant decrease in table game drop but as table games represented such a small portion of drop-in repeater markets, the number of table games dollars lost due to the recession was not practically significant.…”
Section: Discussionsupporting
confidence: 66%
“…Historically, the expansion of commercial casinos passed through two stages (Zheng et al, 2013). The first stage, in response to the Great Depression in 1929, was designed to stimulate the Las Vegas, Nevada economy during the 1930s, leveraging legalized gambling as a strategic method of economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations